A study of carbon black dust and lung function performance among workers at printing industry / Armawaty Natasha Abdul Rahman - Abdul Rahman, Armawaty Natasha (2010)
A comparative cross-sectional study was aimed to assessing lung function performance and respiratory symptoms among printing process workers as consequence of carbon black exposure in printing industry. A questionnaire was used to gain the information on health history and respiratory symptoms of exposed and unexposed group respondent. The carbon black dust concentration was measured using GILLIAN® Sampling Pump (Model GilAir-5'/program- tri-mode air sampler) at flow rate 2.0 L/min with 5 um pore size of PVC filter and 37mm support screen with cassette filter holder. Lung function performance level was carried out on 60 respondents; exposed (n=30), unexposed (n=30) respectively using Vitolograph® Spirometer Model 2120 to measure forced expiratory volume in 1 second (FEVi), forced vital capacity (FVC) and ratio of total volume of air exhaled (FEV]/FVC). Results for the concentration of carbon black dust were at 0.672 mg/m3. Result on lung function performance shown that mean FEVi% predicted of exposed (mean=70.96) and unexposed (mean=83.04). FVC% predicted was 74.3, 13.09 (exposed) and 79.93, 7.10 (unexposed). Identified respiratory symptoms vary among exposed respondent from coughing (63.3%), sore throat (60.0%), nose irritation (53.3%), and mucous dryness (43.3%). In conclusion, lung function performance was lower in FEVi, FVC and FEVi/FVC among exposed group than unexposed group. Results indicated that carbon black dust exposure significantly has an impact on respiratory performances in exposed group. Hierarchy of control is recommended in reducing the dust level in printing room, together with medical health surveillance monitoring on exposed and unexposed group.